The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages REPLY TO THE DISCUSSION DR. GARLAND. This has been an excellent discussion. I am glad someone mentioned welding. It carries with it so many dangers apart from "flash" and the effect on the eyes. There is electrical shock if you do electric welding and there are fumes and heat. Of all workers who face a growing hazard and risk, I would put welders very high in the list. It is time we had more attention paid by the workers themselves to their conditions and more so now that women are coming to play such a part in this work. There are certain precautions that can be taken of course. There are standards of goggles of various specifications to cut out infra-red light and other dangerous rays. But workers must take the responsibility for seeing that these regulations are observed. With regard to milk. It is by law necessary in certain groups in industry. But this does not generally apply and in some cases it is only an agreement with the management to supply milk when it is available. Milk, of course, is just a good food. It has no special preventive qualities such as the power to absorb dust and other poisonous substances. As an example, I was asked by a nurse recently if it was compulsory to have a dust extracting plant in high grinding factories, I replied that it was. But when it was taken up with the manager of her factory he said : "I am supplying milk, what more do you want?" You see the danger of thinking that milk is some special safeguard. It is no substitute for a dust extracter [extractor]. It has no special value except as a food. I am particularly interested to hear the contributions of the miners. I am convinced that the health and safety conditions in mines are far below the standards that could be made possible. There is a very interesting work recently translated into English, which describes the manner in which conditions were improved in the mines of the Donetz Basin in the Soviet Union. It will repay study by all interested in this side of workers' health. One thing I do want to get across to you — that you must have confidence in yourselves. This discussion has shown that workers are on top of these questions and know what they want. For instance the strike which took place recently in Nottinghamshire bears this out. There we had the Miners' Secretary pointing out that the boy directed into the mines was "pit shy." Professor Calpin who is a great authority on such matters, wrote a letter to the "TIMES" in which he showed how correct this was and pointed out that the Miners' Secretary had a far better knowledge of psychology than some of the people who had ordered the lad into the pit. I feel particularly sympathetic towards the comrade who talked about Midwives' difficulties. Here is an excellent example of how workers' organisations should make certain that technical workers in health are getting the equipment thay [they] need to make their service efficient. When we get Socialism, the workers will see to it that such workers are properly equipped and that laboratories and other things exist on the scale required. This should be stressed to professional people who sometimes raise objections to Socialism. Questions of health affect all the people and must be settled by everyone. It lies in our power to make changes and I hope this Conference will mark the turning point in this District and from it organisations of the people will go forward to bring about the changes so urgently needed. 18 15X/2/103/295